The analysis of causality analysis of money supply (M2) and interest rate (BI Rate) in Indonesia: an empirical study in 1990-2021 - Laksono, Roosaleh; Mulyawan, Ferry; Yusuf, Paulus Sugianto (Gema Wiralodra, 2023)
This research investigates the causal relationship between the Bank Indonesia (BI) Rate and the Money Supply (M2) in Indonesia, using annual time series data from 1990 to 2022. The study reveals that an increase in the Money Supply (M2) directly impacts the BI Rate, a policy instrument employed by Bank Indonesia to manage and curb inflation. Moreover, through the rigorous application of Granger Causality Tests, the research demonstrates that the relationship between the BI Rate and Money Supply (M2) is bidirectional. This bidirectional relationship implies that changes in the interest rate influence the money supply and vice versa. These findings provide valuable insights into monetary policy dynamics and its implications for the Indonesian economy.